FTA coordinates study and publication on the Status and Outlook for agroforestry in the Association of Southeast Asian Nations - CGIAR Research Program on Forests, Trees and Agroforestry (2021)
The report presents recommendations pertinent to the needs and interests of ASEAN Member States and aims to motivate actions among ASEAN Ministers and Senior Officials of Agriculture and Forestry along with local resource users, the private sector, researchers and others in expanding the scale of sustainable natural resource management through agroforestry.